Systematic Literature Review: Gap Analysis, Trends, Methodologies, And Innovations of Job Sheet Development for Vocational High School - Galih Kurniawan; Siswantoyo Siswantoyo; Ketut Ima Ismara; Candra Widyastuti (FKIP - Universitas Riau, 2026)
This study aims to analyze trends, innovations, and research gaps in the development of job sheets for vocational education published in Scopus-indexed journals from 2018 to 2023. The methodology used is SLR following the PRISMA guidelines on ten selected articles synthesized to identify development patterns and methodologies. The analysis of these ten studies revealed five main trends: the dominance of the 4-D development model (used by 50% of the studies) and ADDIE (20%), increased integration of digital technology (such as AR, QR codes, virtual laboratories, and animated videos), comprehensive expert validation, emphasis on HOTS, and limitations in effectiveness testing, which was found in only one study. The analytical synthesis revealed significant research gaps, including the lack of longitudinal studies to assess long-term skill retention, limited dissemination stages, and minimal integration of Industry 4.0 competencies and smart technologies like AI. The study concludes that although job sheet development shows rapid advancements in technological and pedagogical aspects, strengthening empirical effectiveness measurements, utilizing immersive technologies, and fostering closer industry collaboration are essential. These findings provide strategic direction for future research to develop more adaptive vocational learning media that aligns with the needs of the global labor market.